2021
DOI: 10.1007/s12640-021-00367-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Regulatory and Molecular Effects of Antidepressants on the Inflamed Human Keratinocyte HaCaT Cell Line

Abstract: Allergic contact dermatitis (ACD) is a T cell-mediated type of skin inflammation resulting from contact hypersensitivity (CHS) to antigens. There is strong comorbidity between ACD and major depression. Keratinocytes release immunomodulatory mediators including pro-inflammatory cytokines and chemokines, which modulate skin inflammation and are crucial cell type for the development of CHS. Our previous studies showed that fluoxetine and desipramine were effective in suppressing CHS in different mouse strains. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…Interestingly, a prior study demonstrated the efficacy of antidepressant drugs in suppressing contact hypersensitivity by attenuating the secretion of proinflammatory molecules, including IL-1β, CCL2, and ICAM-1, in a murine model, which might suggest a shared pathophysiologic pathway between ACD and depression. 17 Notably, we also found an association between ACD and comorbidities that involve sleep disturbance, such as insomnia and daytime somnolence. Sleep impacts daily activities, work productivity, mood, and mental health.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, a prior study demonstrated the efficacy of antidepressant drugs in suppressing contact hypersensitivity by attenuating the secretion of proinflammatory molecules, including IL-1β, CCL2, and ICAM-1, in a murine model, which might suggest a shared pathophysiologic pathway between ACD and depression. 17 Notably, we also found an association between ACD and comorbidities that involve sleep disturbance, such as insomnia and daytime somnolence. Sleep impacts daily activities, work productivity, mood, and mental health.…”
Section: Discussionsupporting
confidence: 52%
“…Patients with ACD used psychiatric medications at higher rates than non-ACD patients. Interestingly, a prior study demonstrated the efficacy of antidepressant drugs in suppressing contact hypersensitivity by attenuating the secretion of proinflammatory molecules, including IL-1β, CCL2, and ICAM-1, in a murine model, which might suggest a shared pathophysiologic pathway between ACD and depression 17 …”
Section: Discussionmentioning
confidence: 99%
“…FX is a widely used antidepressant agent that belongs to the SSRI family. 21 It possesses a remarkable safety profile, 42,43 and it was also shown to exert anti-inflammatory, [23][24][25][26] anti-pruritic, 27,28 prowound healing, 30,31 and anti-AD 32 effects. Thus, it is not surprising that it has already been recommended to treat various diseases and pathological conditions outside of its current indication as an antidepressant.…”
Section: Discussionmentioning
confidence: 99%
“…21 Importantly, besides its 'core' effects on the central nervous system, it has been shown to exert remarkable anti-inflammatory actions in various systems, including the skin. [22][23][24][25][26] Moreover, it has clinically relevant anti-pruritic effects, 27,28 it appears to promote (re)pigmentation of microdissected human hair follicles, 29 it improves wound healing following topical application in diabetic mice 30 as well as in humans with infected wounds, 31 and it was demonstrated to ameliorate AD-like skin lesions in a murine model of AD. 32 Moreover, recent studies demonstrated that, most likely due to direct antiviral and immune regulatory effects, FX administration beneficially influenced the clinical outcome in SARS-CoV-2 infection as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation